Association between breakfast consumption with obesity and physical activity level among adolescents in urban schools of Kota Bharu, Kelantan - Manggis, Mackendy (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Overweight or obesity is the fifth leading risk of death in the world, with their severity and prevalence increases among children and adolescents. This crosssectional study aimed to determine the association between breakfast consumption habit with obesity and physical activity level among adolescents in urban schools of Kota Bharu, Kelantan. The Physical Activity Questionnaire for Older Children (PAQ-C) and a breakfast consumption questionnaire were administered on 200 students of Form 1 and Form 4 in two randomly selected schools. Anthropometric measurements were taken for body weight classification. This study found prevalence for overweight and obesity was 20.5%, where the percentage was higher among females (23.1%). It was also found that 76.5% of the respondent skipped breakfast at least once in a week, and more males (78.3%) skipped breakfast compared to females (75.2%). Only 3% of the respondents were highly active physically, 40% of the respondents were moderately active and 57% were the least active. Mean physical activity score was significantly higher among males (t = 6.58, p - 0.02). This study found no significant association between breakfast consumption and body mass index status and no significant difference of median BMI between breakfast skippers and non-skippers (Z = -0.17, p = 0.87). Similarly, no significant association was found between breakfast consumption and physical activity level. Mean physical activity score was not significantly different between breakfast skippers and non-skippers. In conclusion, awareness about the essential of breakfast eating and physical activity should be disseminated among this age group to prevent some related chronic diseases later in life.